(untitled) (Journal of Forensic Medicine & Toxicology, 2024)
Background: Road traffic accidents are a major epidemic of non-communicable disease in the present century. Among the injuries caused in fatal road traffic accidents, head injuries are most serious injuries to cause mortality and morbidity. Hence the present study was conducted to know the pattern of head injuries in victims of fatal road traffic accident cases. Material & Method: The present study was conducted at the tertiary healthcare centre in southern Haryana. Total of 50 cases of fatal road traffic accident cases with head injuries were enrolled during one year of study period. The basic information about the deceased like age, gender, mode of travel of the victim was obtained from investigating officer narration and inquest papers. During autopsy, detailed examination of injuries was carried out and the autopsy findings were recorded and analyzed. Results: It was observed that out of 50 cases male outnumbered females in ratio 6.14:1. Majority of the victims belonged to the age group 21-30 years. It was observed that among the external injuries over scalp contusion were most common followed by lacerations. It was also observed that intracranial hemorrhages were present in the majority of the victims. Fissured fracture of skull was present in 20% of the victims followed by comminuted fracture 12%. Conclusion: The head injury during road traffic accidents results in mortality, morbidity and disability of the victims. Public attention, awareness, preventive and remedial strategies should be undertaken to control fatal road traffic accidents.